Computer Game Development - Sobota, Branislav (IntechOpen, 2022)
Computer games are a billion-dollar business. In 2021, the value of the gaming industry was about 200 billion US dollars. This book describes some modern approaches, procedures, algorithms, and devices in computer gaming. It includes information on classifications and types of games, technical means of game systems, game consoles, and the newest tools based on extended reality (XR) technologies. Furthermore, the book discusses visualization and 3D computer graphics, game cores (engines) and platforms, genre selection, story design, and trends in game design. It also includes formalizations, algorithms, and tools for a game theory and examines the use of virtual reality and related technologies in modern game user interfaces. Lastly, the book discusses optimizations, testing, and presentations of games and examines the sociological impacts of computer games.